2021
DOI: 10.1177/2045894021996574
|View full text |Cite
|
Sign up to set email alerts
|

The Third Man: DNA sensing as espionage in pulmonary vascular health and disease

Abstract: For as long as nucleic acids have been utilized to vertically and horizontally transfer genetic ma-terial, living organisms have had to develop methods of recognizing cytosolic DNA as either pathogenic (microbial invasion) or physiologic (mitosis and cellular proliferation). Derangement in key signaling molecules involved in these pathways of nucleotide sensing result in a family of diseases labeled interferonopathies. An interferonopathy, characterized by constitutive expres-sion of type I interferons, ultima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 177 publications
(294 reference statements)
0
2
0
Order By: Relevance
“…Notably, a recent study of STING pathway analysis in COVID-19 revealed a pathogenic role for STING, contributing to lung inflammation and disease progression 16 . Likewise, STING promotes inflammation in a variety of disparate disease models [17][18][19] , playing an important role in immune homeostasis 20 , contributing in particular to parenchymal lung disease and systemic vasculitis 21 . To date, there are no data on STING involvement in pulmonary vascular disease, although the role of type I IFN in PH have been addressed by different research groups, albeit with contradicting results 22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…Notably, a recent study of STING pathway analysis in COVID-19 revealed a pathogenic role for STING, contributing to lung inflammation and disease progression 16 . Likewise, STING promotes inflammation in a variety of disparate disease models [17][18][19] , playing an important role in immune homeostasis 20 , contributing in particular to parenchymal lung disease and systemic vasculitis 21 . To date, there are no data on STING involvement in pulmonary vascular disease, although the role of type I IFN in PH have been addressed by different research groups, albeit with contradicting results 22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…16 Likewise, STING promotes inflammation in a variety of disparate disease models, [17][18][19][20] playing an important role in anticipatory immune homeostasis, 21 contributing in particular to parenchymal lung disease and systemic vasculitis. 22 Similarly, STING activation in smooth muscle cells was recently reported to result in cell death, contributing to aortic aneurysm, 23 while STING agonist has been shown to promote apoptosis of tumor endothelial cells in different cancer models. 24 Both studies highlight the relevance of STING in the regulation of cells in the vasculature.…”
mentioning
confidence: 98%